Studi Kasus Sengketa antara Pemilik Tanah HGU dengan Masyarakat dan Upaya Perbaikan Pendaftaran Tanah di Wilayah Simongan - Aprilia Puspitasari Putri Legiman; Najalya Siti Farizqa; Aprilia Niravita; Adymas Hikal Fikri (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This article discusses land disputes over land use rights (HGU) between land owners and the community in the Simongan area, Semarang City. This dispute arises from a lack of legal certainty over the status of land, which has long been managed by local communities. The social, economic and legal impacts of this conflict are significant, including threats to housing, forced relocation and economic inequality. This research also highlights weaknesses in the land registration system which are often the root of problems. Using normative juridical research methods, this article proposes improvements to the land registration system, including the implementation of the Complete Systematic Land Registration (PTSL) program and digitization of land data to prevent similar disputes in the future.